Корреляция фидеистического и антропоморфного начал в художественном тексте - Мизецкая, Вера Ярославовна; Мізецька, Віра Ярославівна; Mizeckaja, Vera (My University, 2013)
The article is devoted to the linguistic and stylistic aspects of the religious motives in the fiction. The modifications of Christ and other figures of the Bible are analyzed in detail in the novels by Ch. Aytmatov, W. Folkner, etc. The anthropomorphic characteristics of the religious images are also considered in the article. Linguistic and poetic peculiarities of the parabolic artistic form, based on the precedent text of the Bible are in the centre of the author's attention as well.
Мизецкая В. Я. Корреляция фидеистического и антропоморфного начал в художественном тексте / В. Я. Мизецкая // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 490-498.
Keywords: фидеистическое начало; антропоморфное начало; художественный текст; притча; архетип; релігійна сутність; антропоморфна сутність; художній текст; religious essence; anthropomorphic essence; fichon; archetype; parabola